Disciplinary Literacy: Virginia School-Based Speech-Language Pathologists' Knowledge and Confidence. (February 2019) - Davis, Karen C.; Murza, Kimberly A.
The purpose of this survey was to examine Speech-Language Pathologists' (SLPs) confidence in their ability to support student outcomes by addressing language-literacy needs, to align therapy to educational standards, and to align therapy to student content areas. A total of 237 school-based SLPs in Virginia completed a 19-item survey. Results indicated school-based SLPs were largely unfamiliar with the concept of disciplinary literacy and only 53% of the respondents indicated that they were " Very confident " or " Somewhat confident " in their ability to align their therapy to students' content areas. Confidence level was found to be negatively correlated with SLPs' experience level ( r s = −.14–−.24, p < .05) and positively correlated with their rating of their education ( r s = .28–.39, p < .01). These results suggest school-based SLPs could benefit from professional development in the area of disciplinary literacy as well as the broader area of adolescent language and literacy interventions.